MOTIVATION AND PARTICIPATION OF FARMERS IN THE AUTP PROGRAM IN SUNGAI PINYUH DISTRICT, MEMPAWAH REGENCY - Sahbudin Sahbudin; Dewi Kurniati; Adi Suyatno (Jurnal Agrisep)
The study's concern is the low number of AUTP participants in Sungai Pinyuh District, so the goal is to examine motivation, participation, and the relationship between motivation and participation. The Likerta scale approach (descriptive) is used to find a relationship in this study, followed by the rang spermant test. Purposive sampling was used to select the research area, which indicates the Sungai Pinyuh sub-district is an active AUTP participant in Mempawah Regency. The number of responses was determined to be as high as 81. The findings of this study show that the level of motivation is in the high category, that the level of participation is also in the high category, that the relationship between motivation and participation is positive, and that research participants should be involved in the evaluation stage to contribute criticism and suggestions.